Nutrition-related practices and attitudes of Kansas skipped-generation(s) caregivers and their grandchildren - Higgins, Mary Meck; Murray, Bethany J. (My University, 2011)
Despite growing numbers, the nutrition practices and attitudes of skipped generation(s) kinship caregivers regarding feeding the dependent children in their care have not been examined. In this qualitative study, transcriptions of semi-structured interviews with 19 female and four male skipped-generation(s) Kansas caregivers (ages 47 to 80, 92% non-Hispanic whites, 83% female, 78% grandparents and 22% great-aunt or great grandparent caregivers; caring for a range of one to four children, ages three to 18, for an average of nine years) were content analyzed for how their nutrition-related practices and attitudes had changed since parenting the first time. Sub-themes regarding practices included: being more nutrition and food safety conscious now, and shifting their child feeding style. The children seemed to be adversely affected by an on-the-go lifestyle and the use of more electronics. Caregivers described their sources for child feeding advice as being based mostly on information from their mothers, physicians, and their past parenting experiences. Sub-themes for attitudes included opinions that nutrition and safe food handling are important and that nutritious food is expensive. They preferred printed or video nutrition education materials and wanted to receive information through organizations they trusted. This population could benefit from education on: infant, child, adolescent, and sports nutrition; feeding “picky eaters”; healthful recipes, “fast foods” and packaged foods; quick, inexpensive meals and snacks low in fat, sugar, and salt; limiting sedentary time; family meals; using food thermometers; and intergenerational gardening and cooking.
Keywords: Grandparents raising grandchildren; Grandfamilies; Grandparent caregivers; Custodial grandparents; Child nutrition; Qualitative research; Nutrition education; Nutrition attitudes; Food safety